Incidental Radiographic Discovery of a Screw in a Primary Molar: An Unusual Case Report in a 6 Year Old Child - Farhin Katge; Sajjad Mithiborwala; Thejokrishna Pammi (Case Reports in Dentistry)
Dentists often find foreign bodies in the primary dentition of children who habitually place objects in their mouths. The objects are frequently embedded in exposures that result from carious or traumatic lesions or from endodontic procedures that have been left open for drainage. Such bodies are often detected on routine radiographs and, less frequently, during clinical examination. We report a case of a 6-year-old boy who had inadvertently embedded a screw in his mandibular right first primary molar and had forgotten about it until it became symptomatic. The screw was impacted in the exposed pulp chamber due to a large carious lesion in the affected molar. This case report considers the possible medical and dental consequences of placing foreign bodies in the mouth.